Challenges in Implementing Islamic Religious Education Learning at a Madrasah in Bengkulu City - Rival Riyuki; Salsabila Salsabila; Utami Artinigsih; Bambang Irawan; Adi Saputra (JMiE (Journal of Management in Education), 2024)
This study examines the learning problems of Islamic Religious Education (IRE) at MTs Bahriyati Qur’anic Boarding School in Bengkulu City. The research aims to identify the forms of obstacles encountered in the IRE learning process, analyze their influencing factors, and understand their implications for learning effectiveness. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving IRE teachers, boarding tutors, and students. The results show that IRE learning problems arise from three interconnected aspects: students’ varied initial abilities and learning fatigue, teachers’ limited use of innovative methods and digital media, and environmental challenges within the boarding system such as dense activity schedules and insufficient learning facilities. These findings indicate that improving IRE learning requires a holistic effort integrating pedagogical strengthening, better learning management, and enhanced technological support.